Appearance of High Endothelial Venule‐Like Vessels in Benign Prostatic Hyperplasia is Associated With Lower Urinary tract Symptoms. Issue 7 (9th February 2017) - Inamura, So; Shinagawa, Tomochika; Hoshino, Hitomi; Sakai, Yasuhiro; Imamura, Yoshiaki; Yokoyama, Osamu; Kobayashi, Motohiro
Abstract : BACKGROUND: Chronic prostatic inflammation is implicated in the pathogenesis of benign prostatic hyperplasia (BPH)‐associated lower urinary tract symptoms (LUTS). Previous studies evaluated the degree of chronic prostatic inflammation based on histological scores, which may contain subjective factors. We previously demonstrated that the number of high endothelial venule (HEV)‐like vessels correlates positively with the magnitude of inflammation in chronic inflammatory gastrointestinal diseases. Here, we evaluated the degree of BPH‐associated chronic prostate inflammation based on appearance of HEV‐like vessels and determined whether the extent of inflammation correlated with LUTS severity, as evaluated by a urodynamic study. METHODS: Eighty‐six BPH tissue specimens derived from patients who had undergone urodynamic analysis were immunostained for CD34 and MECA‐79 to determine HEV‐like vessel number. Triple immunohistochemistry for either CD3 and CD20 or CD4 and CD8, together with MECA‐79, was conducted to identify lymphocyte subsets associated with HEV‐like vessels. We also determined whether the magnitude of chronic prostatic inflammation, as assessed by HEV‐like vessel number, correlated with the degree of LUTS. RESULTS: HEV‐like vessels were induced in lymphoid aggregates seen frequently in BPH. The number of HEV‐like vessels positively correlated not only with the magnitude of chronic prostatic inflammation but also with the degree of LUTS, particularly with symptoms associated with voiding function, which was measured objectively in a pressure flow study. CONCLUSIONS: Chronic prostate inflammation may promote BPH and resulting voiding dysfunction. Assessment of the number of HEV‐like vessels could be a surrogate for identifying the degree of chronic prostatic inflammation. Prostate 77:794–802, 2017 . © 2017 Wiley Periodicals, Inc.